2013
DOI: 10.1038/ni.2523
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional reprogramming of mature CD4+ helper T cells generates distinct MHC class II–restricted cytotoxic T lymphocytes

Abstract: TCRαβ thymocytes differentiate to either CD8αβ cytotoxic T lymphocytes or CD4+ T helper cells. This functional dichotomy is controlled by key transcription factors, including the T helper master regulator, ThPOK, which suppresses the cytolytic program in MHC class II-restricted CD4+ thymocytes. ThPOK continues to repress CD8-lineage genes in mature CD4+ T cells, even as they differentiate to T helper effector subsets. Here we show that the T helper-fate was not fixed and that mature antigen-stimulated CD4+ T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
420
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(471 citation statements)
references
References 48 publications
25
420
1
1
Order By: Relevance
“…Moreover, absence of TGF-β signaling did not greatly impact antiviral cytokine secretion by D b :GP 33-41 LCMV-specific CD8 T cells upon cognate peptide stimulation (Supplemental Figure 1D). We also found that TGF-β signaling only minimally suppressed the effector markers KLRG and Ly6C on virus-specific CD8 T cells, or granzyme B on IFN-γ-producing cells, after GP [33][34][35][36][37][38][39][40][41] peptide stimulation (Supplemental Figure 1, E-G). Overall, these data show that deletion of Tgfbr2 prior to infection only minimally affected CD8 T cell antiviral responses early after chronic LCMV infection.…”
Section: Cellmentioning
confidence: 99%
“…Moreover, absence of TGF-β signaling did not greatly impact antiviral cytokine secretion by D b :GP 33-41 LCMV-specific CD8 T cells upon cognate peptide stimulation (Supplemental Figure 1D). We also found that TGF-β signaling only minimally suppressed the effector markers KLRG and Ly6C on virus-specific CD8 T cells, or granzyme B on IFN-γ-producing cells, after GP [33][34][35][36][37][38][39][40][41] peptide stimulation (Supplemental Figure 1, E-G). Overall, these data show that deletion of Tgfbr2 prior to infection only minimally affected CD8 T cell antiviral responses early after chronic LCMV infection.…”
Section: Cellmentioning
confidence: 99%
“…This includes CD4 T cell responses against carbohydrate epitopes (62). A recent report found that conventional Th1 CD4 T cells can be converted into cytolytic CD4 T cells by reducing the expression of the transcription factor ThPOK (63).…”
Section: Cd4 T Cells Mediate Tumor Protectionmentioning
confidence: 99%
“…46 However, recent studies found cytotoxic CD4 C T cells may represent a separate polarized functional subset of CD4 C T cells. 36,[47][48][49] The cytotoxic activity of the CD4 C T cells we identified was blocked by MHC class II antibody and CMA, indicating that the cytotoxic CD4 C T cells used the perforin pathway to kill tumors. 50 Since lymphoma and myeloma are B-cell tumors, which express both MHC class I and II alleles on the cell surface, the cytotoxic CD4…”
Section: E1232220-12mentioning
confidence: 95%